Shaping Positive Character: Implementation of the Kampus Mengajar 5 Programme MBKM in Preventing Bullying, Sexual Violence, and Drug Abuse at SDN 8 Palu: Membentuk Karakter Positif: Implementasi Program Kampus Mengajar 5 MBKM dalam Pencegahan Perundungan, Kekerasan Seksual, dan Penyalahgunaan Narkoba di Lingkungan SDN 8 Palu - Ahmar, Dewi Satria; Diah, Anang Wahid M.; Yasin, Yusril; Zulkifli, Zulkifli; Syafitri, Dhini; Rizki, Nur Riani; Sari, Sintya Puspita (Yayasan Ahmar Cendekia Indonesia, 2023)
Bullying, sexual violence, and drug abuse are behaviors that currently attract the attention of education observers. Many of these behaviors occur in school-age children including in elementary schools. Therefore, one of the efforts made to minimize the development of this is by conducting socialization. The socialization activities carried out by the service team are an initial step to protect and prevent bullying, sexual violence, and drug abuse in schools. This socialization aims to provide information to students about the types of bullying, sexual violence, and drug abuse, and actions that can be taken to avoid or prevent these things so that the final result expected from this socialization activity is the formation of positive characters from students to prevent and avoid these behaviors. This socialization activity is integrated with one of the student programs from the Tadulako University campus who participated in Campus Teaching Batch 5 assigned to SDN 8 Palu.